Systematic Review: Analysis of Factors Shaping Safety Culture in the Mining Industry - Sri Yuli Rahayu; Novrikasari Novrikasari; Hamzah Hasyim (GLOBAL HEALTH SCIENCE GROUP, 2024)
The mining industry plays an important role in economic development, but also presents significant occupational safety risks. Strengthening safety culture is crucial to protect workers and ensure the sustainability of company operations. This study aims to analyze the main factors that shape safety culture in the mining sector through a systematic review approach. This research method follows the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines by reviewing relevant literature published in the last five years. The analysis identified five main factors that influence safety culture: (1) management commitment, (2) safety training, (3) worker involvement, (4) effective communication, and (5) safe working environment. Strong management commitment has been shown to improve the provision of safety resources, such as personal protective equipment (PPE) and consistent supervision. Regular and innovative safety training can improve worker compliance with safety procedures. Active involvement of workers in safety-related decision-making promotes a sense of shared responsibility. Effective communication between management and workers improves understanding of occupational risks and safety procedures. In addition, ergonomic work environments and standardized equipment reduce the potential for accidents. This research confirms the importance of a holistic approach in strengthening safety culture in the mining industry. The integration of management leadership, comprehensive training, worker involvement, good communication, and supporting infrastructure are key in minimizing workplace accidents and creating a strong safety culture.